Alongamento ativo excêntrico dos músculos flexores do joelho na postura em pé: efeito sobre a amplitude de movimento e torque muscular - Batista, Lucia Helena (Universidade Federal de São Carlos, 2005)
The relation between flexibility alterations and muscular torque posstretching is not so exploited in literature. There are many stretching techniques and posture used in clinics and sportive activities. The technique of eccentric active stretching in a standing posture, with weight unloading in the stretched limb, is one of them. Thus, a better knowledge of the alterations caused after its application will provide scientific support for its usage. Objective: To evaluate the effects of an eccentric active stretching program of the knee flexor muscles in the standing posture on the evaluated limb on: knee extension ROM, passive torque of knee flexor muscles and isometric and isokinetic concentric and eccentric torque of flexor and extensor muscles of the knee. Methodology: 34 healthy and sedentary volunteers, both genders (34,42 ± 9,3 years) were evaluated. All of them had 20° or more knee flexor muscles shortening. The stretching program was performed twice a week, for four weeks and consisted of 7 consecutive repetitions of 1 min each one with a 30s rest between them. Knee ROM and knee torque were evaluated using an Isokinetic Dynamometer before and after four weeks of intervention. The passive torque and knee ROM were measured passively, while the isometric, concentric and eccentric torque of the flexor and extensor of the knee were measured through maximal voluntary contractions (speeds 30°/s, 60°/s). Results: There was an increase in the knee extensor ROM from 53,7 ± 13° to 30,1 ± 16° (p = 0,0001). No alteration occurred in the passive torque (from 11,2 ± 3N to 10,6 ± 3N; p = 0,09). The isometric extensor and flexor torque increased from 68 ± 67,8N to 187,58 ± 73,5N (p = 0,006) and from 89,68 ± 32,62N to 93,87 ± 33,12N (p = 0,01), respectively. There was a gain of knee extensor concentric torque at 60°/s from 144,44 ± 51,6N to 151,57 ± 58,2N (p = 0,02) and knee extensor eccentric torque at 30°/s from 175,4 ± 71,6N to 189,9 ± 73,8N (p = 0,01). There was an improvement in the flexor eccentric and concentric torque at 30º /s (from 100,3 ± 34,2N to 105,63 ± 35N; p = 0,02 and from 90,7 ± 31,7N to 96,7 ± 31,8N; p = 0,001, respectively). Conclusions: The eccentric active stretching program of the knee flexor muscles in a standing posture was effective to increase knee extension ROM, improving flexibility in the knee flexor muscles, although there was no change in the passive torque. It also improved the isometric and isokinetic peak torque from the muscle group submitted to the stretching and its antagonist group.
Active stret ching program of the knee flexor muscle in a standing posture: effect on the ROM and muscle torque
Keywords: Exercícios terapêuticos; Alongamento (Fisiologia); Torque muscular; Alongamento excêntrico; Eccentric stretching; Flexibility; Flexor muscles; Knee; ROM; Muscle torque; Passive torque; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL